The ESDP and the transatlantic relationship - Volker Heise (Stiftung Wissenschaft und Politik (SWP), 2007)
Security relations between the US and the EU are limited largely to policy on Iran and the Middle East. In the US view a direct link with ESDP is not necessary, since its security co-operation with Europe can take place via NATO. For the Europeans, too, NATO provides the main forum for transatlantic security relations, while they see the ESDP as an instrument for the EU to act independently of the US. Co-operating indirectly through NATO is not an entirely satisfactory option, since this channel is hampered by cumbersome procedures, and consultations are currently blocked by the dispute over Cyprus. Direct co-operation between the US and EU would therefore present an alternative.This study sets out to highlight differences between the US and European approaches to crisis management and to explore possibilities for more intensive co-operation. Specifically it looks at: * strategic policies * civil and military capabilities * the willingness and mechanisms for mutual co-operation.The two sides' security strategies differ mainly in the importance attached to military instruments as a means of crisis management and in attitudes to pre-emption, prevention and multilateralism. Recognizing that its resources are overstretched, the US has begun to see the advantages of burden-sharing. Hence, discussion with US opinion leaders should aim to identify common bases for action. Given their complementary capabilities, close co-operation could raise the effectiveness of US and EU engagement. Current consultations are complicated by the variety of EU structures and competencies and are therefore rather unproductive. While the expansion of the competencies of EU's High Representative may improve coherence within the EU, to be able to speak and act for the EU he or she would need still broader powers. This would require the EU states to anchor their national security policies more firmly in the European framework. (SWP - Studie / SWP)
Keywords: 320